IMPLEMENTATION OF THE DRIVING SCHOOL (SEKOLAH PENGGERAK) AND DRIVING TEACHERS (GURU PENGGERAK) PROGRAM AS EDUCATIONAL INNOVATION IN THE SOCIETY 5.0 ERA - Nor Rochmatul Wachidah; Habibie, M. Luqmanul Hakim; Nur Syamsiah; Nasution, Sri Purwanti (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
In the Society 5.0 era, educational challenges have become increasingly complex, requiring innovations that support school transformation and the improvement of teacher quality. The Driving School Program and Driving Teachers Program are Indonesia's government responses to these needs. The School Empowerment Program aims to digitalize schools, strengthen governance, and create a more interactive and technology-adaptive learning environment. Meanwhile, the Teacher Empowerment Program focuses on human resource development through continuous training and study comparisons, aiming to enhance teachers' skills and competencies in facing the demands of the digital era. Teachers are expected to become agents of change capable of applying innovations within school environments, improving collaboration, and leading the educational transformation process. This research uses a literature review method, analyzing various relevant sources regarding the implementation of these two programs. The results show that these programs positively impact the improvement of teachers' competencies, particularly in mastering technology and teaching methodologies relevant to Society 5.0. Additionally, the implementation of the School Empowerment Program supports the role of schools in enhancing the quality of education through digitalization and innovation. Thus, the School Empowerment Program and Teacher Empowerment Program can be considered significant innovations in preparing Indonesia's young generation to compete in the continuously evolving digital era. Keywords: Digitalization; Driving School; Driving Teachers; Education Innovation; Society 5.0.   Abstrak Di era Society 5.0, tantangan pendidikan semakin kompleks, memerlukan inovasi yang mendukung transformasi sekolah dan peningkatan kualitas guru. Program Sekolah Penggerak dan Guru Penggerak merupakan respon pemerintah Indonesia terhadap kebutuhan ini. Program Sekolah Penggerak bertujuan untuk mendigitalisasi sekolah, memperkuat tata kelola, dan menciptakan lingkungan belajar yang lebih interaktif dan adaptif terhadap teknologi. Di sisi lain, Program Guru Penggerak berfokus pada pengembangan sumber daya manusia melalui pelatihan dan studi banding berkelanjutan, yang bertujuan untuk meningkatkan keterampilan dan kompetensi guru dalam menghadapi tuntutan era digital. Guru diharapkan menjadi agen perubahan yang mampu menerapkan inovasi di lingkungan sekolah, meningkatkan kolaborasi, serta memimpin dalam proses transformasi pendidikan. Penelitian ini menggunakan metode studi literatur, dengan menganalisis berbagai sumber yang relevan mengenai implementasi kedua program tersebut. Hasil penelitian menunjukkan bahwa program ini mampu memberikan dampak positif dalam peningkatan kompetensi guru, terutama dalam hal penguasaan teknologi dan metodologi pembelajaran yang relevan dengan Society 5.0. Selain itu, implementasi Program Sekolah Penggerak juga mendukung peran sekolah dalam meningkatkan kualitas pendidikan melalui digitalisasi dan inovasi. Program Sekolah Penggerak dan Guru Penggerak dapat dianggap sebagai inovasi penting yang mempersiapkan generasi muda Indonesia untuk berkompetisi di era digital yang terus berkembang. Kata Kunci: Digitalisasi; Guru Penggerak; Inovasi Pendidikan; Sekolah Penggerak; Society 5.0.